Design Method and Finite Element Analysis of Prefabricated Steel-concrete Composite Lattice Column. Issue 1 (October 2020) - Fu, Xiaofan; Peng, Xiaotong; Zhang, Xu; Lin, Chen
Abstract: In order to solve the problem of exposed column, a new prefabricated steel-concrete composite lattice column (SCLC) in residential building was proposed. The SCLC consists of concrete filled steel tubes, which are connected by channel steel and lace plates. The finite element simulations of six infilled SCLC with different cross-section (L-shaped, T-shaped and X-shaped) were performed under monotonic loading by using ABAQUS, in which the carrying capacity, ductility, stiffness and energy dissipation were analysed. The results indicate that the infilled concrete can improve the strength and stiffness of SCLC, while the ductility decreases slightly. X-shaped SCLC has the best carrying capacity and poor ductility. The SCLC with T-shaped has the best comprehensive performance.